Analysis of Problem-Solving Ability of Junior High School Students in A System of Linear Equations With One Variable - Hafizah, Nur; Nurhalimah, Siti; Utami, Wahyu Lestari; Angraini, Lilis Marina (International Journal of Contemporary Studies in Education, 2025)
This research is motivated by the low ability of students to solve mathematical problems, which is reflected in the results of surveys and previous research. Even though mathematics is considered an important subject, many students still experience difficulties in understanding and solving mathematical problems, including solving problems with systems of linear equations in one variable. The research method used is descriptive with a quantitative approach. This research aims to describe and analyze students' problem solving abilities. The subjects used were 30 selected class VIII students at Al-Faruqi Middle School. Data was collected through tests, then analyzed to identify student errors in solving problems on systems of linear equations in one variable. The results of the research show that the majority of students experience difficulty in understanding basic concepts, are less thorough in the problem solving process, have difficulty understanding problem questions, and have difficulty allocating time when working on questions. Based on data analysis, the percentage of student errors is classified as moderate. From these results, it is concluded that further efforts are still needed to improve students' mathematical problem solving abilities, especially in the context of one-variable linear equation systems. This can be done by focusing more on identifying factors that cause student errors and developing learning strategies that are more effective in improving students' understanding and problem solving skills in mathematics.